Inclusive Insurance Sector: An Innovative Business Model for Micro-Insurance Delivery in Sri Lanka - Heenkenda, Shirantha (Journal of Asian Business Strategy, 2016)
The core objective of this study is to explore the feasibility of farmers‟ organizations (FOs) as a vehicle for micro-insurance delivery of the paddy crop, grown by small-scale (peasant) farmers in Sri Lanka. Factor Analysis was used to elicit the group dynamic and the capacity of FOs as a stakeholder in the insurance supply chain. The results show that the farmers‟ organizations are most widespread and are a very close institutional setup for paddy farmers because FOs are capable of handling financial activities with transparency, and have healthy financial habits and as a result farmers participate actively in farmers‟ organization activities. This study provided clear policy insights for the policy makers to implement an innovative business model for micro-insurance delivery to be incorporated with the FO model in Sri Lanka. Furthermore, it was revealed that the postal network can act as a financial intermediary in circumstances to assist the FOs in financial activities, where the commercial insurers do not have an outlet or branch networks in their target area. Therefore, in order to develop the links between the farmers and the insurers, it seems viable that the public-private partnership model be used for micro-insurance supply to paddy farmers in Sri Lanka.